2021
DOI: 10.1111/1365-2656.13460
|View full text |Cite
|
Sign up to set email alerts
|

The earlier the better? Nesting timing and reproductive success in subalpine cavity‐nesting bees

Abstract: Reproductive timing can affect an organism's production of offspring and its offspring's success, both of which contribute to its overall fitness. In seasonal environments, the timing of reproductive activity may be restricted to short periods of the year owing to numerous potential selective pressures such as variation in daylength, weather, food availability, predation or competition. We documented the relationships between reproductive timing and individual reproductive success (total reproductive output an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…How environmental variation influences different stages of an organism's life cycle and to what extent successive stages of the life cycle are linked are critical for predicting population and community responses to environmental change. This is especially the case for wild pollinators because we currently know relatively little about the factors driving their demography and thus population dynamics (Roulston & Goodell, 2011; but see Boggs & Inouye, 2012; Crone & Williams, 2016; Wong & Forrest, 2021). Animal pollinators are ecologically and economically important (Klein et al, 2007; Ollerton et al, 2011), but many populations are undergoing declines world‐wide (Cameron & Sadd, 2020; Potts et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…How environmental variation influences different stages of an organism's life cycle and to what extent successive stages of the life cycle are linked are critical for predicting population and community responses to environmental change. This is especially the case for wild pollinators because we currently know relatively little about the factors driving their demography and thus population dynamics (Roulston & Goodell, 2011; but see Boggs & Inouye, 2012; Crone & Williams, 2016; Wong & Forrest, 2021). Animal pollinators are ecologically and economically important (Klein et al, 2007; Ollerton et al, 2011), but many populations are undergoing declines world‐wide (Cameron & Sadd, 2020; Potts et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, two major hypothesised mechanisms underlying observed global pollinator declines are reduced food resources (Potts et al, 2016; Woodard & Jha, 2017), and changing climate conditions (Crossley et al, 2021; Soroye et al, 2020), which can have both direct effects on pollinator survival and indirect effects on floral resource availability (Ogilvie et al, 2017; Thomson, 2016). Although climate and resource conditions define the most basic requirements for pollinator populations, these two factors are often studied in isolation (but see Ogilvie et al, 2017; Wong & Forrest, 2021) and their effects across different life stages in pollinator life cycles are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…We currently know relatively little about the factors driving the demography and thus population dynamics of wild pollinators (Roulston & Goodell, 2011; but see Boggs & Inouye, 2012; Crone & Williams, 2016; Wong & Forrest, 2021)—despite the critical ecosystem services pollinators provide (Roubik, 1995; Kremen et al, 2002; Klein et al, 2007; Garibaldi et al, 2013) and their widely observed declines (Goulson et al, 2015; Potts et al, 2016). The abundance of different pollinator life stages can be influenced by climate conditions experienced, the availability of floral food resources, and the success (as assessed e.g., by abundance) of previous life stages.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, because males in our communities were not able to disperse after mating, they may have harassed females, interrupting their nesting and provisioning behaviour. Under warmer conditions, female solitary bees may produce more brood cells, as was the case in our warmed communities where 10 times as many brood cells were produced, but higher temperatures may also be linked to reduced bee lifespan, translating into reduced reproductive output (Wong & Forrest, 2021 ). Lastly, the bees we used may not have been adapted to our ambient conditions, which were likely warmer than those experienced in their source populations, potentially reducing male bee fertility and attractiveness (Martinet et al, 2021 ) and female nesting success (Pitts‐Singer et al, 2014 ) across treatments.…”
Section: Discussionmentioning
confidence: 85%